The Mechanism Switching the Osteoclast From Short to Long Duration Bone Resorption - Delaisse, Jean-Marie; Søe, Kent; Andersen, Thomas Levin; Rojek, Aleksandra Maria; Marcussen, Niels (Frontiers in Cell and Developmental Biology, 2021)
The current models of osteoclastic bone resorption focus on immobile osteoclasts sitting on the bone surface and drilling a pit into the bone matrix. It recently appeared that many osteoclasts also enlarge their pit by moving across the bone surface while resorbing. Drilling a pit thus represents only the start of a resorption event of much larger amplitude. This prolonged resorption activity significantly contributes to pathological bone destruction, but the mechanism whereby the osteoclast engages in this process does not have an answer within the standard bone resorption models. Herein, we review observations that lead to envision how prolonged resorption is possible through simultaneous resorption and migration. According to the standard pit model, the “sealing zone” which surrounds the ruffled border (i.e. the actual resorption apparatus), “anchors” the ruffled border against the bone surface to be resorbed. Herein, we highlight that continuation of resorption demands that the sealing zone “glides” inside the cavity. Thereby, the sealing zone emerges as the structure responsible for orienting and displacing the ruffled border, e.g. directing resorption against the cavity wall. Importantly, sealing zone displacement stringently requires thorough collagen removal from the cavity wall - which renders high cathepsin K collagenolysis indispensable for engagement of osteoclasts in cavity-enlargement. Furthermore, the sealing zone is associated with generation of new ruffled border at the leading edge, thereby allowing the ruffled border to move ahead. The sealing zone and ruffled border displacements are coordinated with the migration of the cell body, shown to be under control of lamellipodia at the leading edge and of the release of resorption products at the rear. We propose that bone resorption demands more attention to osteoclastic models integrating resorption and migration activities into just one cell phenotype.